Diagnostic Value of Systematic Imaging Examination in Embedded Optic Disc Drusen in Adolescents with Mild Visual Impairment - Xiuhua Jia; Tiancheng Bao; Shasha Wang; Ting Jiang; Zhijian Zhong; Yanling Zhang; Qigen Li; Xiang Zhu (Journal of Ophthalmology)
Aim. To evaluate the diagnostic value of systematic ophthalmologic imaging examination in the diagnosis of embedded optic disc drusen (ODD) in adolescents with mild visual impairment. Methods. Eleven patients were evaluated through optometric examination, fundus photography, visual field inspection, optical coherence tomography (OCT), ultrasonography (US), and fundus fluorescein angiography (FFA). Of the 11 patients, three also underwent cranial and orbital magnetic resonance imaging (MRI). Results. All 11 patients had either no apparent abnormality or only mild refractive abnormalities. In all patients, fundus inspection revealed flushing the optic disc with varying degrees of limited boundary ambiguity and optic disc congestion with disappearance of the fovea. One patient had a visual field defect during the period of edema of ODD, but the visual field returned to normal after the optic disc edema subsided. US revealed discoid acousto-optic masses in front of the optic disc in six patients. OCT showed a slight elevation and thinning of the retinal nerve fiber layer (RNFL) of the optic disc in all patients. Quasicircular, hyperreflex signals of different sizes could be observed below the RNFL. Late-stage FFA revealed focal staining at the edge of the optic disc without fluorescence leakage in all patients. Orbital and cranial MRI findings were normal in the three patients. Conclusion. A systematic ophthalmologic imaging examination can not only improve the detection rate of embedded ODD but also avoid excessive examinations and treatments.